Appropriateness of therapeutic and informative communication to the health literacy level of health service users - Kekuš Divna; Stanisavljević Sanja; Joković Sandra (Association of Nurses Technicians and Midwives, 2017)
Health literacy implies the knowledge, motivation, and competence of an individual to find, understand, evaluate and apply health information for the purpose of judging and making decisions about health. In the field of health literacy three levels of functionality are distinguished: functional (basic), interactive and critical health literacy. The assessment of the health literacy level is carried out by standardized instruments such as: REALM (Rapid Estimate of Adult Literacy in Medicine), WRAT (Wide Range Achievement Test), CLOZE test, TOFHLA (Test of Functional Health Literacy in Adults) and NVS test (The Newest Vital Sign). The contemporary concept of health places health literacy in health resources as a factor that contributes to increasing health potential, and therefore quality of life as well. The importance of the appropriateness of therapeutic and informative communication in the daily work of health workers is reflected in the assessment of the level of health literacy of the users and the application of adequate methods and techniques of communication in the provision of health services, especially in dealing with vulnerable groups and groups at risk.